The Interrelationship of Calvin’s John Commentary and the 1559 Institutes on the Lord’s Supper - Budhi, Yohanes (JURNAL TEOLOGI REFORMED INDONESIA, 2021)
Esai ini memeriksa perkembangan tafsir Calvin atas Perjamuan Kudus dari John Commentary (1553) hingga Institutes edisi 1559, serta menunjukkan keterkaitan antara kedua karya tersebut Esai ini berargumen bahwa John Commentary Calvin memberikan pengaruh yang berarti bagi Ins-titutes edisi 1559. Kuatnya keterkaitan ini secara khusus terlihat dari antara tafsiran Calvin atas Yohanes 6 dalam John Commentary dan Institutes edisi 1559 bagian IV.xvii. Dalam kedua karya ini, Calvin memberi penekanan atas Perjamuan Kudus dengan menggunakan Yohanes 6. Dari sini tampak jelas bagaimana John Commentary memengaruhi formasi doktrin Calvin mengenai Perjamuan Kudus di dalam Institutes edisi 1559. This paper examines how Calvin’s interpretation of the Lord’s Supper was developed from his John Commentary (1553) to the 1559 Institutes, and shows the interrelationship between the Insti-tutes and his John Commentary. This paper argues that his John Commentary had a significant influ-ence in the 1559 Institutes. There is a strong interrelationship between Calvin’s John Commentary (especially on John 6) and his 1559 Institutes (especially in IV.xvii). In both works, Calvin used John 6 in the strong emphasis on the Lord’s Supper. Clearly, his John Commentary influenced the formation of the doctrine of the Lord’s Supper in the 1559 Institutes.